Linguistic Politeness of Qatari Emir’s Political Speech Sheikh Tamim Bin Hamad Al-Thani - Fauzi, Muhammad; Muta'ali, Abdul (Proceedings of AICS - Social Sciences, 2018)
This research was based on Qatari Emir’s speech, Sheikh Tamim bin Hamad Al-Thani on July 21, 2017, that still preferred to use polite language, although Saudi Arabia, the United Arab Emirates, Bahrain, and Egypt discontinued their diplomatic relations with Qatar and executed embargo it and on June 5, 2017. This research was aimed to analyze the language politeness in Qatari Emir’s speech and reveal the intention of its use. The theory used in this research was Brown and Levinson’s politeness theory (1987) which relates the speech politeness with face threatening act (FTA) and classifies them into four kinds namely strategy on record without redressive action-baldly, strategy on record with redressive action-positive politeness, strategy on record with redressive action-negative politeness, and strategy off record. The method used in this research was qualitative-descriptive. The data analyzed in this research was Qatari Emir’s speech text on July 21, 2017 which officially sourced from the government of Qatar. Based on the findings of this research, the writer identified 26 politeness speech with 4 on record without redressive action-baldly strategy, 5 positive politeness strategy, 14 negative politeness strategy, and 3 off-record strategy. The numerous use of negative politeness compared with other strategies on Qatari Emir’s speech showed that Qatari Emir responded the act of its four neighboring countries by negative attitudes and negative feelings such as rejection, anger and satire yet still maintaining the relationship. Besides, the number of positive politeness showed that Qatari Emir still considered the friendliness and closeness in its relationship with its four neighboring countries.Keywords:Politeness, Qatari Emir, speech.